The Correlation between Serum Albumin Level with Ischemic Stroke Prognosis at Dr. Moewardi Hospital, Surakarta - VANNY SCARLETT VALENTINE; Suratno .; Lukman Aryoseto (Nexus Kedokteran Klinik, 2015)
Background: Stroke can cause brain damage that ends up as a serious long-term disability. Some previous research mentioned that albumin as a neuroprotector in ischemic stroke. Albumin can improve ischemic stroke prognosis by anti-edema effects, hemodilution effects, and antioxidants effects. Methods: This study is an analytical observational research with a cross sectional approach. The amount of sample in this study is 32 ischemic stroke patients at Dr. Moewardi Hospital, Surakarta were selected by simple random sampling. The sample were selected according to both inclusive and exclusive criteria that determined by the researcher. The dependent variable in this study is ischemic stroke prognosis, the independent variable is serum albumin level, and confounding variable are age, stroke severity degree, premorbid conditions, and post-stroke complications. Researcher gives the explanation and helps the patients to fill (1) Biodata form and informed consent, (2) Serum albumin level, ages, stroke severity degree, premorbid conditions, and post-stroke complications, and (3) Barthel Index. The collective data were analyzed using the Spearman Test and then processed with odds ratio calculation. Then, confounding variable was calculated with binary logistic regression analysis. Result: Using Spearman Test obtained value (p) = 0,04 and a correlation coefficient of serum albumin level and ischemic stroke prognosis was 0.313. Based on the calculation, the value of odds ratio is 4.000 with Confidence of Interval is 0,828 19,325 (RO = 4,000, CI = 0,828 19,325). The result of binary logistic regression analysis was known that influential variable in ischemic stroke prognosis is stroke severity degree (RO = 36,000) and post-stroke complication (RO = 3.441.206.744). With constant at 23,463, obtained the equation: . Conclusion: There is a statistically significant relationship between serum albumin level with ischemic stroke prognosis at Dr. Moewardi Hospital, Surakarta. Patient with low level serum albumin has 4 times greater suffered worse ischemic stroke prognosis than patients with normal serum albumin level. Keywords: Albumin, stroke ischemic prognosis